2008
DOI: 10.2139/ssrn.1142623
|View full text |Cite
|
Sign up to set email alerts
|

Friendships Moderate an Association Between a Dopamine Gene Variant and Political Ideology

Abstract: Scholars in many fields have long noted the importance of social context in the development of political ideology. Recent work suggests that political ideology also has a heritable component, but no specific gene variant or combination of variants associated with political ideology have so far been identified. Here, we hypothesize that individuals with a genetic predisposition toward seeking out new experiences will tend to be more liberal, but only if they are embedded in a social context that provides them w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 127 publications
1
42
0
1
Order By: Relevance
“…Research in political science is beginning to take seriously that this is indeed the case. A small but growing literature in the discipline has found consistent evidence that political attitudes and behaviors are at least partially heritable (e.g., Alford, Funk, & Hibbing, 2005;Hatemi, Gillespie, Hibbing, Alford, & Martin, 2008;Hatemi et al, 2010), and other studies have reported correlations between specific genes and political phenotypes (e.g., Settle, Dawes, Christakis, & Fowler, 2008).…”
mentioning
confidence: 99%
“…Research in political science is beginning to take seriously that this is indeed the case. A small but growing literature in the discipline has found consistent evidence that political attitudes and behaviors are at least partially heritable (e.g., Alford, Funk, & Hibbing, 2005;Hatemi, Gillespie, Hibbing, Alford, & Martin, 2008;Hatemi et al, 2010), and other studies have reported correlations between specific genes and political phenotypes (e.g., Settle, Dawes, Christakis, & Fowler, 2008).…”
mentioning
confidence: 99%
“…Using the AddHealth data, DeLisi et al (2008) report an association between DRD4 polymorphisms and age of first criminal arrest among adolescents from low risk families, but not among high risk families. Settle et al (2010) found that among participants in the NLSAH with the D4 7-repeat allele, the number of friendships in adolescence was significantly associated with liberal political ideology, while there was no such association among those without the gene variant. Sasaki et al (2013) show that the influence of priming participants with religion positively affects the willingness to volunteer for environmental causes among those who carry the D4 2 or 7-repeat allele but not among those carrying other variants.…”
Section: (B) Drd4 Genesmentioning
confidence: 91%
“…In the appendix (Appendix 5) we present results that show Democrats and Republicans do not have significantly different distributions of the A2 allele, suggesting we will need to look elsewhere for genes that may be associated with political orientations. One such possiblity has been suggested by Settle et al (2008).…”
Section: Case-control Designmentioning
confidence: 97%